Association of ABO blood groups and ART outcomes among subfertile South Asian women: a retrospective cohort study - Nithya Panapakkam Jayakumar; Karuppusami Reka; Chinta Parimala; Aleyamma Thayparmbil Kunjummen; Mohan Shashikant Kamath (Middle East Fertility Society Journal, 2022)
Abstract Background Blood groups are expressed on the surface of the red cells, and their association with the ovarian reserve and pregnancy outcomes has been an area of interest. The aim of the current study is to study the association of blood groups with live birth rates among South Asian women undergoing assisted reproductive technology treatment. It is a retrospective cohort analysis of women undergoing assisted reproductive technology (ART) at Christian Medical College and Hospital, India, between January 2007 and June 2017. All women ≤ 40 years undergoing the first ART cycle with fresh embryo transfer were included and stratified into four groups (A, B, AB, and O) based on the blood group type. The ART outcomes were analyzed among the groups. Results A total of 2524 women underwent fresh embryo transfer cycles during the study period, among whom 2079 women were analyzed. There was no statistically significant difference in the live birth rates for women with blood group B (odds ratio, OR 0.96, confidence interval, CI, 95% 0.74–1.24), blood group AB (OR 0.89, 95% CI 0.58–1.35), and blood group O (OR 0.87, 95% CI 0.68–1.12) with blood group A as the reference. After adjusting for important confounders, there was no statistically significant difference in the live birth rates for women with blood group B, AB, and O in comparison with blood group A. Conclusion The current study showed no association of blood groups with the ART treatment outcomes in South Asian women.